PENGARUH PELATIHAN DIGITAL OLEH RUMAH BUMN TERHADAP PENINGKATAN KINERJA UMKM BINAAN DI KABUPATEN SIDENRENG RAPPANG - Muh. Imran Awal; Muhammad Rusdi; Rahman Yakub; Andi Riska Andreani Syafaruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the still-limited capability of Micro, Small, and Medium Enterprises (MSMEs) in utilizing digital technology to support business development, particularly in semi-rural areas such as Sidenreng Rappang Regency. This study aims to analyze the influence of digital training organized by Rumah BUMN on the performance improvement of assisted MSMEs in Sidenreng Rappang Regency. A quantitative approach with an associative research design was employed. The population consisted of 224 MSMEs fostered by Rumah BUMN Sidenreng Rappang, with a sample of 144 respondents determined using the Slovin formula. Data were collected through a five-point Likert-scale questionnaire, observation, and documentation, and analyzed using SPSS through validity and reliability tests, classical assumption tests, simple linear regression analysis, the coefficient of determination, and hypothesis testing (t-test). The results show that digital training has a positive and significant effect on the performance improvement of MSMEs fostered by Rumah BUMN, with a significance value of 0.000 (< 0.05), thus the research hypothesis is accepted. The regression coefficient of 0.295 indicates that every improvement in digital training is followed by an improvement in MSME performance, while the coefficient of determination (R²) of 0.280 indicates that digital training explains 28.0% of the variation in MSME performance improvement, with the remaining 72.0% explained by other factors outside the research model. These findings indicate that the digital training programs organized by Rumah BUMN need to be continuously strengthened to drive a more significant improvement in MSME performance.